The Influence Of The Personal And Social Responsibility Teaching Model (TPSR) And The Cooperative Model On Life Proficiency In Physical, Sport And Health Education - Haidzar Fauzan Muharam; Dian Budiana; Agus Mahendra (JUARA : Jurnal Olahraga, 2023)
Life skills as skills needed to overcome the demands and demands of everyday life to see an increase in life skills in research students used two learning models, namely the Teaching Personal and Social Responsibility (TPSR) model and the cooperative model. The purpose of this study was to find out how much influence the Teaching Personal and Social Responsibility (TPSR) model and cooperative model had on life skills in physical education, sports and health. The research method in this study is to use a comparative experimental method, comparative research to find out whether two variables or more than two groups have differences in the aspects or variables studied. The experimental research design used in this study was the Pretest-Posttest Control Group Design. The samples used in this study were 15 students in the TPSR group and 15 students in the cooperative group. With the application of the TPSR learning model which aims to improve aspects of students' life skills, the average pretest score = 150.13 and the posttest average score = 166.40 with a difference in score of 16.27. As for the cooperative learning model which aims to improve aspects of students' life skills, the average pretest score = 112.27 and the posttest average score = 158.33 with a difference in score of 46.07. Thus, the difference in the average value of the TPSR learning model is smaller than the difference in the average value of the cooperative learning model, so that it can be concluded that the cooperative learning model has more influence on students' life skills.